Effectiveness of CRSCE-Based De-escalation Training on Reducing Physical Restraint in Psychiatric Hospitals: A Cluster Randomized Controlled Trial - Ye, Junrong; Xia, Zhichun; Wang, Chen; Liao, Yao; Xu, Yu; Zhang, Yunlei; Yu, Lin; Li, Sijue; Lin, Jiankui; Xiao, Aixiang (Frontiers in Psychiatry, 2021)
Background The use of physical restraint (PR) causes clinical and ethical issues; great efforts are being made to reduce the use of PR in psychiatric hospitals globally. Aim This study aimed to examine the effectiveness of CRSCE-based de-escalation training on reducing PR in psychiatric hospitals. Method The proposed study adopted cluster randomized controlled trial design. Twelve wards of a psychiatric hospital were randomly allocated to experimental group (n=6) and control group (n=6). Wards of control group were assigned to routine training regarding PR; wards of experimental group underwent the same routine training while additionally received CRSCE-based de-escalation training. Before and after CRSCE-based de-escalation training, the frequency of and the duration of PR, and the numbers and level of unexpected events caused by PR, were recorded. Results After CRSCE-based de-escalation training, the frequency (inpatients and patients admitted within 24 hours) of and the duration of PR of experimental group, showed a descending trend and were significantly lower than those of control group (P<0.01); compared to control group, the numbers of unexpected events (level Ⅱ and level Ⅲ) and injury caused by PR of experimental group had been markedly reduced (P<0.05). Conclusions CRSCE-based de-escalation training would be useful to reduce the use of PR and the unexpected event caused by PR in psychiatric hospitals. The modules of CRSCE-based de-escalation training can be adopted for future intervention minimizing clinical use of PR.